LABORATORY TRIAL OF PROTEIN DETERMINATION IN URINE USING DIFFERENT PH VALUES OF ACETIC ACID AND ACETATE BUFFER METHOD - Dinar Rahayu; Tuti Rustiana (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2020)
Abstract The determination of protein in urine is important in clinical examination along with other parameters in urine. The presence of protein in urine can be interpreted that there is a disorder in kidney. Acid and heat coagulations method is still widely used in many areas to determine protein in urine. In this method, the characteristic of protein that will precipitate in the presence of acid or if exposed to heat is deployed to gain information about the amount of protein. The greater amount of protein, the more prominence is the coagulation. Urine pH also varies according to the condition, classic acidosis will give an acidic urine and the presence of ammonium producing bacteria can cause basic urine. In this research acetic acid method with 6% of CH3COOH and pH value of 2,9 and buffer acetic with pH 4,5 are used to determine the certain amount of protein (+3 value, corresponds with 2-4 mg/dL protein in urine) in varied pH values of urine samples. To compare the results, first in control urine with pH 6,8 the results of both methods is compared and shows no significant different, then the Kruskall-Wallis test is used to compare the results in other pH values to control and the test is shown also there are no significant difference. This shows that either acetic acid at pH 2,9 or acetic buffer at pH 4,5 can be used to determine protein amount in urine.